2020
DOI: 10.5812/ijp.97680
|View full text |Cite
|
Sign up to set email alerts
|

Prealbumin May Predict Clinical Outcomes in Children with Severe Mycoplasma pneumoniae Pneumonia

Abstract: Background: Serum prealbumin (PA) levels have been found to have prognostic value in patients with infectious diseases. Objectives: We aimed to determine the relationship between PA levels and clinical outcomes in children with severe Mycoplasma pneumoniae pneumonia (MPP). Methods: We retrospectively reviewed the data of 163 children with severe MPP who were treated in our hospital from January 2015 to December 2017. The demographic and clinical data of the subjects were collected and statistically analyzed.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A PA ≤144.5 mg/L was associated with BMP formation in children with MPP. PA is a negative acute phase protein synthesized by the liver and is a non-specific host defense [15]. In addition, it was found that earlier use of corticosteroid (CS) therapy can reduce the formation of BMP in children with MPP.…”
Section: Discussionmentioning
confidence: 99%
“…A PA ≤144.5 mg/L was associated with BMP formation in children with MPP. PA is a negative acute phase protein synthesized by the liver and is a non-specific host defense [15]. In addition, it was found that earlier use of corticosteroid (CS) therapy can reduce the formation of BMP in children with MPP.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al compared Mycoplasma pneumoniae (MP)-associated PB cases with an MP-associated non-PB patient group and reported higher CRP and erythrocyte sedimentation rate levels in the patient group. 9 The authors suggested that this could be used as an indicator of airway mucus embolism in children with MP. In support of this hypothesis, we thought that in our study, an increase in acute phase reactants due to viral infections may lead to airway rigid mucus plugs by increasing inflammation and edema formation.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with CRP, PA can effectively improve the diagnostic e ciency of children's CAP and assess the severity of pneumonia [17]. Research by Wang et al showed that the PA level can re ect the severity of severe MPP, suggesting that the PA level may become an objective indicator for predicting the progress of severe MPP [18].…”
Section: Discussionmentioning
confidence: 99%